The Effects of Brand Image, Review Beauty Vlogger, and Product Quality on Purchase Decisions for Wardah Cosmetics - Novi Saputri; Khoirul Hikmah (Universitas Mercu Buana, 2023)
This study is aimed at analyzing the effect of Brand Image , Review Vlogger, and Product Quality on Purchase Decisions for Wardah Cosmetics at Female Management Study Program Students of UPN